IS THERE A DIFFERENCE IN BALANCE FUNCTIONS BETWEEN BREAST CANCER SURVIVOR WOMEN AND HEALTHY WOMEN? - Ozdemir, Ferdiye Zabit; Iyigun, Gozde (Turkey Assoc Physiotherapists, 2022)
Purpose: Breast cancer survivors have various physical problems and balance disorders after mastectomy surgery (BCS). The study aimed to compare the balance functions in BCS women who had a mastectomy with healthy women. Methods: Sixty-six individuals, BCS women who had a mastectomy (BCS group, n=33) and healthy women (control group, n=33), were included in the study. In this study, subjective balance problems and falling characteristics, static balance (Tandem Romberg Test - TRT) and dynamic balance (Y Balance Test- (YBT) and computer-based dynamic balance platform - Technobody-PK 200 WL) functions of the study and control groups were compared. Results: The individuals in the BCS group (48.48%) experienced more balance problems than the control group (6.06%), but there was no difference between the two groups in terms of falling characteristics. Static balance (TRT) eyes-closed results were lower in the BCS group than the control group (t=-2.21, p=0.03), but there was no difference between the groups in TRT eyes-open results. There was no difference in any sub-parameter in dynamic balance measurements between the groups. Conclusion: Subjective balance problems and static balance functions are affected more in BCS than in healthy individuals. It is recommended that balance functions should be evaluated and followed up with appropriate treatment methods in BCS women who had a mastectomy.
Keywords: Breast Cancer; Falling; Mastectomy; Postural Balance